ACCURATE POWER ANALYSIS FOR CONVENTIONAL MOS TRANSISTORS USING 0.12Âµm TECHNOLOGY - Durrani, Y. A. (The Nucleus, 2013)
Power dissipation of very large scale integrated circuits (VLSI) has emerged as a significant constraint on the semiconductor industry. For the dynamic power the voltage, capacitance and frequency are the major components of the power dissipation. In this paper, we propose a new power macromodeling technique for the power estimation of conventional metal-oxide- semiconductor (MOS) transistors. As the dynamic power is directly linked with the load capacitance (CL), it is also a lumped capacitance of all internal parasitic capacitances. In our proposed model, we take an account of the parasitic capacitances with their dependence on channel width and the length. Suitable values of other factors (i.e. threshold voltage VT, gate voltage VGS, drain voltage VDD etc.) are used for the power consumption of the MOS transistors. The Preliminary results are effective and our macromodel provides the accurate power estimation.